Comparison of hspX gene sequence in the Beijing and non-Beijing Mycobacterium tuberculosis. (December 2020) - Seyed Majidi, Ashkan; Bazzazi, Hadi; Zamani, Samin; Ghaemi, Ezzat Allah
Abstract: Purpose: The pathogenicity of various lineages of Mycobacterium tuberculosis (MTB) is different. This could be due to the difference in survival ability within the host macrophage. The alpha crystalline secretion protein, a product of the hspx gene, is one of the bacterial protection factors in these stressful situations. The Beijing family, part of the East Asian lineage, was reported to be more virulent. Regarding the importance of this protein in pathogenicity, this study was conducted to investigate the polymorphism of the hspx gene in Beijing family compared to non- Beijing strains. Method: DNA of 50 MTB isolates were extracted by boiling method. The existence of hspx gene was determined using PCR-specific primer and finally PCR product was sequenced to examine the polymorphism in both direct and reverse directions. Sequencing results were aligned by chromas software. Results: The hspx gene was detected in all of the Beijing and non-Beijing isolates. The polymorphism in the sequences of this gene were not observed in all of the MTB isolates. Discussion: This study indicated that hspx gene is protected. Also it has showed that lineage type was not related to the sequence of hspX gene, but the expression of this protein may be different, which requires further studies.